Authorial voice in academic writing - Yin Ling Cheung; Louwena Lau (Ibérica, 2020)
Academic writers represent themselves in their texts in different ways, notably through use of first person pronouns to construct an authorial voice and enhance arguments. This study examines how expert writers in the disciplines of Literature and Computer Science use first person pronouns. The hypothesis is that in the absence of objective fact, Literature writers resort to frequent use of first person pronouns backed by stronger authorial roles to build credibility and convince readers, while Computer Science writers avoid first person pronouns in line with conventional wisdom in the hard sciences. The findings suggest that the general dichotomy between hard and soft sciences regarding first person pronouns usage may not apply in all cases. Our study discusses the similarities and differences in the disciplinary conventions in Literature and Computer Science, thus making contributions towards pedagogy and scholarship of the role of first person pronouns in voice construction in academic texts